Knowledge and awareness of sepsis among orthopaedic patients in Hospital Universiti Sains Malaysia (Hospital USM) - Aziz, Norsyafieka (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2020)
Asepsis can cause mortality due to the infection and one of the medical emergencies that need early identification. The objectives of study were to determine the level of knowledge and awareness of sepsis among orthopaedic patients in Hospital USM. This study also examined the association of knowledge of sepsis with gender and level of education. A total of 74 orthopedic patient who were hospitalized were recruited in this study using a simple random sampling method. Data were collected from December 2019 to February 2020 using self-administered questionnaires and analysed using SPSS version 23.0. Descriptive statistics was used to analysed for mean, SD, frequency, percentage and Pearson’s Chi Square. Ethical approval was obtained from Human Research Ethics Committee (JEPeM) of USM. The findings revealed that overall knowledge level of sepsis among orthopaedic patient was at high level with M=21.797, SD=5.221. Overall level of awareness of sepsis among orthopaedic patients in Hospital USM were at higher level with M=3.351, SD=0.783. The study found that gender was not significance association with level of knowledge of sepsis (p=0.184). However, level of education was significant association with score of knowledge of sepsis among orthopaedic patients (p=0.05). The result of this study can be used as a baseline information to determine and improves level of knowledge and awareness towards sepsis prevention either among orthopaedic patients or other patients.